The Effect of Filtration with Natural Esker Sand on the Removal of Organic Carbon and Suspended Solids from the Effluent of Experimental Recirculating Aquaculture Systems - Lindroos, Antti-Jussi; Lindholm-Lehto, Petra; Pulkkinen, Jani; Kiuru, Tapio; Vielma, Jouni (Springer Science and Business Media LLC, 2020)
We studied the effect of sand filtration with natural esker material on the removal of total organic carbon (TOC), total suspended solids (TSS), and turbidity from the effluent of an experimental recirculating aquaculture system (RAS) farm. Separate experiments were performed with the same esker sand: (1) a soil column experiment in 2017 where the effluent (mean TOC 8.14 mg L−1) was percolated vertically through a 50-cm-thick sand column with the infiltration 1 m day−1; (2) a sand filtration experiment with watersaturated conditions in 2018 where the effluent from the woodchip denitrification (mean TOC 26.84 mg L−1) was infiltrated through a sand layer with the retention time of 1.2 days. In experiment 2, infiltration of 25 L day−1 through a 31-cm sand layer and 40 L day−1 through a 50-cm sand layer were studied. Both experiments were performed in association with rainbow trout (Oncorhynchus mykiss) grow-out trials. In sand filtration with vertical water flow through a soil column, the removal of TSS was 40%, while of TOC 6%, partly due to the small thickness of the soil column and coarse sand material. In water-saturated conditions, mean removal of TOC (3 mg L−1 1.2 day−1), TSS (1.2 mg L−1 1.2 day−1), and turbidity (0.4 FTU 1.2 day−1) reached 11% (TOC), 18% (TSS), and 15% (turbidity), even with the retention time of only 1.2 days. The removal of TOC in water-saturated conditions correlated with the removal of TSS and turbidity.
Keywords: Effluent; Recirculating aquaculture system (RAS); Total organic carbon (TOC); Total suspended solids (TSS); Turbidity; Sand filtration